‘I’ve no fear of dying alone’: exploring perspectives on living and dying alone - Caswell, Glenys; O'Connor, Morna (Taylor & Francis, 2017)
Dying alone is portrayed as undesirable in terms of policy, health and social care provision, the wishes of family and friends, and in popular culture. Despite this, people do often die alone, both in institutional and domestic settings. This paper reports findings from a study which explored ways of investigating individuals’ perspectives on dying alone at home. It tested methods of recruitment and data collection, gathered preliminary data and explored the ethical issues involved. Interviews with 11 older people living alone and seven hospice at home nurses are reported here. For the older people, the idea of dying alone was less problematic than the idea of needing care and support from others, and the perceived loss of independence that this would entail. Participants reacted in differing ways to threats to their independence, but all utilised a form of relational reflexivity when considering the effect their actions might have on others. The nurses would prefer no one to die alone, but believed they had seen patients managing their own dying so that they could be alone at the moment of death. The paper suggests that dying alone may be a problem for survivors, rather than for the person who is dying.